ANALYSIS OF M. QURAISH SHIHAB ON THE UTILIZATION OF RAINWATER FOR ENVIRONMENTAL CONSERVATION IN AL-QUR'AN - Fitriani, Fitriani; Hamidah , Tutik (Antis Publisher, 2024)
Objective: This study examines M. Quraish Shihab’s interpretation of Quranic verses related to rainwater in Tafsir al-Misbah, focusing on its implications for sustainability, particularly soil fertility, agriculture, and groundwater management. Rainwater plays a crucial role in environmental preservation, supporting agriculture, water conservation, and ecosystem health. In Islamic teachings, rain is a manifestation of Allah's mercy and sustenance, frequently highlighted in the Quran. Method: Employing a qualitative approach, the study analyzes Shihab’s interpretation of key Quranic verses, including Surah an-Nahl (16:65), Fussilat (41:39), al-Baqarah (2:22), and al-An’am (6:99), to explore the theological and practical dimensions of rainwater utilization. Results: Shihab’s exegesis underscores rainwater's vital role in reviving barren land, producing fruits, supporting plant growth, and mitigating environmental degradation. His analysis highlights rainwater as a resource that aligns with sustainable practices, such as reducing soil erosion, conserving water, and improving air quality. Novelty: The study bridges Quranic exegesis with contemporary sustainability discourse, contributing to the emerging field of Islamic environmental ethics. It provides a foundation for promoting eco-friendly practices grounded in religious teachings, offering actionable insights for policymakers, environmentalists, and Islamic scholars to integrate ecological stewardship with divine mandates.